2000
DOI: 10.1161/01.str.31.9.2043
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Raised Plasma Osmolality on Clinical Outcome After Acute Stroke

Abstract: Background and Purpose-Abnormal physiological parameters after acute stroke may induce early neurological deterioration. Studies of the effect of dehydration on stroke outcome are limited. We examined the association of raised plasma osmolality on stroke outcome at 3 months and the change of plasma osmolality with hydration during the first week after stroke. Methods-Acute stroke patients had their plasma osmolality measured at admission and at days 1, 3, and 7. Maximum plasma osmolality and the area under cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
135
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(147 citation statements)
references
References 29 publications
7
135
0
3
Order By: Relevance
“…Insufficient fluid intake may lead to dehydration, which in turn can have a significant negative impact on physical and cognitive function, overall recovery and quality of life [2]. Dehydration is particularly concerning for patients in the acute phase following stroke as it may affect the ischaemic penumbra, induce neurological deterioration, and influence the evolution of the stroke itself [3] and is associated with poorer outcomes at hospital discharge with regard to survival rate and dependency [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Insufficient fluid intake may lead to dehydration, which in turn can have a significant negative impact on physical and cognitive function, overall recovery and quality of life [2]. Dehydration is particularly concerning for patients in the acute phase following stroke as it may affect the ischaemic penumbra, induce neurological deterioration, and influence the evolution of the stroke itself [3] and is associated with poorer outcomes at hospital discharge with regard to survival rate and dependency [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…4 In our country, there are many studies on stroke, its associated conditions and their effect on stroke patient's outcome, but a few studies on electrolytes disturbance in stroke patients has been done in our country, even outside. 9 In this study, I attempted to find out the common electrolytes disturbances in acute stroke patients and its effect on the immediate outcome of the patients.…”
mentioning
confidence: 99%
“…It is observed that specialized services for the treatment of stroke (stroke units) make use of a more aggressive intravenous hydration. Hypotonic fluids, however, can bring harm, as they elevate the risk of cerebral edema and intracranial hypertension, especially in extensive infarcts 65,66 . Hyperglycemia occurs in more than half of the patients in the acute phase of stroke, even the ones with no history of diabetes mellitus, and it is associated with increased morbidity and mortality, regardless of age, the mechanism of ischemic stroke or the extent of the ischemic injury.…”
Section: Stroke In the Emergency Departmentmentioning
confidence: 99%